Detection of immunolabels with multi-isotope imaging mass spectrometry (MIMS) - Thiery-Lavenant, G. (Surf Interface Anal, 2014)
We have developed a method that combines the use of stable isotopes, MIMS and antibody. We began with using well-established antibodies, anti-actin and anti-synaptophysin, in mouse intestinal cells. We extended the method to an immunogold assay to specifically localize Ribeye, a major protein component of retina synaptic ribbons, or to localize a synaptic vesicle-containing protein, synaptophysin. Both are localized in presynaptic nerve terminal of photoreceptors cells in retina. Our results show that by MIMS analysis of the Au signal we can directly identify antibodies tagged with non amplified 1.4 nm gold nanoparticles. They also demonstrate that the gold nanoparticle-tagged antibodies do not dilute the (15)N/(14)N signal used for measuring protein turnover. Thus we can simultaneously and directly use MIMS to measure protein turnover and to identify cell type or specific protein.